Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, Leverage, Dan Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern - Natalia, Lidya; Sugara, Kathryn (GEMA EKONOMI, 2023)
This study aims to determine whether there is an effect of company size, profitability, liquidity, leverage, and company growth on Going concern audit opinion. The type of research used is quantitative. sampling technique of this research is to use a purposive sampling method with a sample of 122 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The data analysis technique uses logistic regression analysis with SPSS 26 test equipment. The results of this study indicate that company size and liquidity have a significant negative effect on going-concern audit opinion, while profitability, leverage and company growth have no significant effect on going-concern audit opinion.